Rūznāmah-i safar-i Khurāsān - Ḥakīm al-Mamālik, ʻAlī Naqī ibn Ismāʻīl, 19th cent (Intishārāt-i farhang-i Īrān zamīn, 1977)
Account of the travel of Nāsir al-Dīn Shāh, Chah of Iran, 1831-1896, to Khorasan, Iran.